THE USE OF BOXED MEDIA ON FATHER'S SOLAR MATTER TO ENHANCE THE CRITICAL THINKING CAPACITY OF SCHOLARS - Azwar Rahmat; Nyimas Umi Kalsum, Choirun Niswah; Yuda Septian Kurniawan (International Journal of Teaching and Learning, 2024)
One of the essential things in the Merdeka Curriculum in order to improve the basic education system in Indonesia is the combination of Natural Sciences (IPA) and Social Sciences (IPS) subjects into Natural and Social Sciences (IPAS). This research aims to determine the improvement and description of the application of smart used box media to students' critical thinking abilities. The research method used is qualitative research, which aims to obtain more complete and in-depth data, so that the research objectives can be achieved and uses three cycles with data collection techniques of observation, interviews and documentation. Students' critical thinking skills can be obtained by using media or simple learning resources that contain information/phenomena of daily life and have potential problems that can be explored by students and involve a particular subject matter. It can be seen that with this media, SD Negeri 43 students can improve their abilities. critical thinking.